Molecular and Crystal Structure of 7,7-Dimethyl-2-pyridin-4-yl-6,7-dihydro-1,2,4-triazolo[1,5-a][1,3,5]triazin-5-amine [1] - Dolzhenko, Anton; Tan, G.; Koh, L.; Dolzhenko, A.; Chui, W. (MDPI, 2011)
When crystallized from ethanol, 7,7-dimethyl-2-pyridin-4-yl-6,7-dihydro-1,2,4-triazolo[1,5-a][1,3,5]triazin-5-amine forms crystals which have monoclinic (P21/n) symmetry with unit cell dimensions a = 7.3326(5) Å, b = 19.4897(14) Å, c = 8.6586(6) Å, α = 90°, β = 106.069(2)°, γ = 90°, V = 1189.06(14) Å3, Z = 4. The triazine ring in the molecule has a flattened boat conformation with gem-dimethyl groups as flagpole and bowsprit at the bow. The puckering parameters for the ring are: Q = 0.2996(14) Å, θ = 111.7(3)° and φ = 124.1(3)°. In the crystal, molecules are arranged in the three types of chains generated by the intermolecular NH···N hydrogen bonds. The extended chains with the C(11) graph-set motif running along a [010] axis are formed by the amino group hydrogen atom and the pyridine nitrogen atom of another molecule. The C(4)C(6) chains with the R22(8) binary graph-set motif running along a [101] direction are formed by linking the amino group hydrogen atom and the hydrogen atom at the triazine nitrogen atom with the triazole and triazine nitrogen atoms of another molecule, respectively. The centrosymmetric inverted dimers are formed via the C-H···π interactions between the methyl group hydrogen and the pyridine ring of the pair molecule.